Research Progress on Cardiac Tissue Construction of Mesenchymal Stem Cells for Myocardial Infarction - Yang, Guo-Dong; Ma, Da-Shi; Ma, Chun-Ye; Bai, Yang (Current Stem Cell Research & Therapy, 2024)
Heart failure is still the main complication affecting the prognosis of acute myocardial infarction (AMI), and mesenchymal stem cells (MSCs) are an effective treatment to replace necrotic myocardium and improve cardiac functioning. However, the transplant survival rate of MSCs still presents challenges. In this review, the biological characteristics of MSCs, the progress of mechanism research in the treatment of myocardial infarction, and the advances in improving the transplant survival rate of MSCs in the replacement of necrotic myocardial infarction are systematically described. From a basic to advanced clinical research, MSC transplants have evolved from a pure injection, an exosome injection, the genetic modification of MSCs prior to injection to the cardiac tissue engineering of MSC patch grafting. This study shows that MSCs have wide clinical applications in the treatment of AMI, suggesting improved myocardial tissue creation. A broader clinical application prospect will be explored and developed to improve the survival rate of MSC transplants and myocardial vascularization.
Keywords: Acute myocardial infarction